2021
DOI: 10.1002/cbin.11665
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory repercussions in female steroid responsive glands after perinatal exposure to bisphenol A and 17‐β estradiol

Abstract: The mammary gland (MG) and female prostate are plastic reproductive organs which are highly responsive to hormones. Thus, endocrine disruptors, such as bisphenol A (BPA) and exogenous estrogens, negatively affect glandular homeostasis. In addition to previously described alterations, changes in inflammatory markers expression also trigger the development of a microenvironment that contributes to tumor progression. The current work aimed to evaluate the inflammatory responses of the MG and prostate gland to BPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…61 Hyperandrogenism was positively related to the increased BPA levels in 12 studies. The hyperandrogenism in the studies is in alignment with the changes that BPA causes: direct stimulation of ovarian theca cells to secrete androgens; 62,63 alteration of the hypothalamic-pituitary-gonadal axis with severe damage to gonadotroph cells; 64 alteration of the steroid feedback at the hypothalamic-pituitary level and steroid action at the ovarian level, reducing hypothalamic-pituitary-ovarian axis function; 65,66 increases the expression of cytochrome P450 17α-hydroxylase (CYP17A1), an enzyme that participates in androgen production in the gonads and adrenal cortex, and alters its gene expression in granulosa cells; 67 reduces P450 aromatase, slowing down the transformation of testosterone into 17β-estradiol; 42,68 binds to sex-hormone-binding globulin displacing steroids and increasing free testosterone 69 and upregulates the gene expression involved in the androgen biosynthesis pathway. 70 Takeuchi and Tsutsumi 36 found higher BPA levels in healthy men and in patients with PCOS than in the control women; they raised two hypotheses for their findings-the production of testosterone is stimulated by BPA or androgens negatively regulate uridine diphosphate-glucuronosyl transferase activity impairing BPA metabolism.…”
Section: Discussionmentioning
confidence: 91%
“…61 Hyperandrogenism was positively related to the increased BPA levels in 12 studies. The hyperandrogenism in the studies is in alignment with the changes that BPA causes: direct stimulation of ovarian theca cells to secrete androgens; 62,63 alteration of the hypothalamic-pituitary-gonadal axis with severe damage to gonadotroph cells; 64 alteration of the steroid feedback at the hypothalamic-pituitary level and steroid action at the ovarian level, reducing hypothalamic-pituitary-ovarian axis function; 65,66 increases the expression of cytochrome P450 17α-hydroxylase (CYP17A1), an enzyme that participates in androgen production in the gonads and adrenal cortex, and alters its gene expression in granulosa cells; 67 reduces P450 aromatase, slowing down the transformation of testosterone into 17β-estradiol; 42,68 binds to sex-hormone-binding globulin displacing steroids and increasing free testosterone 69 and upregulates the gene expression involved in the androgen biosynthesis pathway. 70 Takeuchi and Tsutsumi 36 found higher BPA levels in healthy men and in patients with PCOS than in the control women; they raised two hypotheses for their findings-the production of testosterone is stimulated by BPA or androgens negatively regulate uridine diphosphate-glucuronosyl transferase activity impairing BPA metabolism.…”
Section: Discussionmentioning
confidence: 91%
“…In these phases an intense remodeling occurs in epithelial and stromal compartments (Terry et al, 2019) and exposure to BPA triggers a late tumor development onset at aging (Ruiz, Colleta, Leonel, et al, 2021). Also, recent studies have shown that BPA acts as an inflammatory modulator in MG in adult females exposed in utero (Leonel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%